\(\frac{x+1}{18}+\frac{x+2}{17}=\frac{x+5}{14}+\frac{x+4}{15}\)
\(\Rightarrow\frac{x+1}{18}+1+\frac{x+2}{17}+1=\frac{x+5}{14}+1+\frac{x+4}{15}+1\)
\(\Rightarrow\frac{x+1}{18}+\frac{18}{18}+\frac{x+2}{17}+\frac{17}{17}=\frac{x+5}{14}+\frac{14}{14}+\frac{x+4}{15}+\frac{15}{15}\)
\(\Rightarrow\frac{x+19}{18}+\frac{x+19}{17}=\frac{x+19}{14}+\frac{x+19}{15}\)
\(\Rightarrow\frac{x+19}{18}+\frac{x+19}{17}-\frac{x+19}{14}-\frac{x+19}{15}=0\)
\(\Rightarrow\left(x+19\right).\left(\frac{1}{18}+\frac{1}{17}-\frac{1}{14}-\frac{1}{15}\right)=0\)
\(\text{Mà }\left(\frac{1}{18}+\frac{1}{17}-\frac{1}{14}-\frac{1}{15}\right)\ne0\text{ nên: }x+19=0\Rightarrow x=-19\)